Problem Talk in Management Group Meetings. (December 2019) - Laapotti, Tomi; Mikkola, Leena
This naturalistic study focuses on problem talk (PT) in hospital management group meetings. The study aims to understand how PT constitutes the hospital organization through the different uses of PT within the meetings, and, therefore, to understand the organizing role of these meetings. The communication as constitutive of organization (CCO) perspective forms the theoretical background of the research. The results of the qualitative analysis show that PT comprises many intertwined tasks that aim to perform the meetings, enhance problem solving, and maintain the relational level of group life. Thus, PT is much more than merely solving problems. In PT, problems are discussed from the viewpoints of the group and the organization. Meetings as an institution and as a nonhuman agent affect organizing because they influence both the group's communication and organizational processes. Future research on groups should develop the use of the CCO concept of nonhuman agency.